2009
DOI: 10.1103/physreva.79.021606
|View full text |Cite
|
Sign up to set email alerts
|

Atom-atom correlations in colliding Bose-Einstein condensates

Abstract: We analyze atom-atom correlations in the s-wave scattering halo of two colliding condensates. By developing a simple perturbative approach, we obtain explicit analytic results for the collinear ͑CL͒ and back-toback ͑BB͒ correlations corresponding to realistic density profiles of the colliding condensates with interactions. The results in the short-time limit are in agreement with the first-principles simulations using the positive-P representation and provide analytic insights into the experimental observation… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
112
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(118 citation statements)
references
References 17 publications
6
112
0
Order By: Relevance
“…A similar behavior is seen in the CL correlation width, except that it starts For longer durations of dissociation-while still within the range of validity of the undepleted molecular-field approximation-we see that the BB correlation width grows faster (for bosons) than the CL correlation width, indicating the possibility that it may eventually become broader than the CL width. A similar behavior has been recently found in first-principle simulations of a related system of atomic four-wave mixing via condensate collisions [46]. Moreover, it has been shown that in the long-time limit the BB correlation width indeed becomes broader than the CL correlation, in agreement with the experimental measurements of Ref.…”
Section: Width Of the Correlation Functionssupporting
confidence: 90%
“…A similar behavior is seen in the CL correlation width, except that it starts For longer durations of dissociation-while still within the range of validity of the undepleted molecular-field approximation-we see that the BB correlation width grows faster (for bosons) than the CL correlation width, indicating the possibility that it may eventually become broader than the CL width. A similar behavior has been recently found in first-principle simulations of a related system of atomic four-wave mixing via condensate collisions [46]. Moreover, it has been shown that in the long-time limit the BB correlation width indeed becomes broader than the CL correlation, in agreement with the experimental measurements of Ref.…”
Section: Width Of the Correlation Functionssupporting
confidence: 90%
“…This can, in principle, be achieved with, e.g., an ∼5 times larger value of the coupling G; however, for the same trap frequencies, such a large value of G would require an ∼5 times larger peak density ρ 0 (0) of the source condensate. The respective initial total atom number in this case would have to be N ∼ 5 × 10 6 [due to the Thomas-Fermi scaling of N ∝ ρ 0 (0) 5/2 ], which is about 50 times larger than in the experiment.…”
Section: Anisotropy Time Scalesmentioning
confidence: 81%
“…[3,6]. The undepleted pump refers to the source condensate, which will be assumed to stay constant in time.…”
Section: Simple Quantum Treatment: Relation To Parametric Down-comentioning
confidence: 99%
See 1 more Smart Citation
“…Atomic four-wave mixing [15] has long been considered a possible method of creating entanglement between spatially separated atomic modes [16][17][18][19][20][21][22][23], and the generation and detection of quantum correlations using this process has recently been demonstrated [24,25]. Four-wave mixing has an advantage over one-axis-twisting schemes because the correlations produced by the interaction are number correlations and are not as sensitive to the total number of particles.…”
Section: Introductionmentioning
confidence: 99%